2008
DOI: 10.1007/bf03086144
|View full text |Cite
|
Sign up to set email alerts
|

Chest pain in the emergency room: value of the HEART score

Abstract: Background. Chest pain is one of the most common causes of presentation to the emergency room. The diagnosis of non-ST-elevation acute coronary syndrome typically causes uncertainty. Classical considerations for risk stratification are History, ECG, Age, Risk factors and Troponin (HEART). Each can be scored with zero, one or two points, depending on the extent of the abnormality. The HEART score is the sum of these five considerations. Methods. Clinical data from 122 patients referred to the emergency room for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
598
7
11

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 531 publications
(626 citation statements)
references
References 11 publications
10
598
7
11
Order By: Relevance
“…Several risk scores have been developed, including Thrombolysis in Myocardial Infarction (TIMI); [4][5][6] Global Registry of Acute Coronary Events (GRACE); [7][8][9][10] Fast Revascularisation in Instability in Coronary disease (FRISC); 11 and History, ECG, Age, Risk factors, and Troponin (HEART), 12,13 to identify which patients with chest pain of cardiac etiology are at higher risk for worse cardiovascular outcomes and mortality. These scores are derived from overlapping clinical variables recorded at time of evaluation, including age, vital signs, comorbidities, and biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Several risk scores have been developed, including Thrombolysis in Myocardial Infarction (TIMI); [4][5][6] Global Registry of Acute Coronary Events (GRACE); [7][8][9][10] Fast Revascularisation in Instability in Coronary disease (FRISC); 11 and History, ECG, Age, Risk factors, and Troponin (HEART), 12,13 to identify which patients with chest pain of cardiac etiology are at higher risk for worse cardiovascular outcomes and mortality. These scores are derived from overlapping clinical variables recorded at time of evaluation, including age, vital signs, comorbidities, and biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…The HEART score algorithm13 is depicted in Table 1. The HEART score was retrospectively determined based on patient data recorded at time of presentation to the ED.…”
Section: Methodsmentioning
confidence: 99%
“…Myocardial necrosis can often be confirmed or excluded within 1 to 3 hours,11, 12 but the interpretation of troponin levels depends on clinical context and repeated measurements. The HEART score13, 14 is a simple and effective clinical prediction rule incorporating both clinical context— H istory, E lectrocardiograph, A ge and R isk factors—and admission T roponin levels. Using solely information collected at time of presentation, the HEART score is able to accurately estimate a patient's short‐term cardiac risk, taking into account not only the risk of myocardial infarction during the index visit, but also major adverse cardiac events (MACE) that occur in the first 6 weeks thereafter.…”
Section: Introductionmentioning
confidence: 99%
“…in comparison to the other previous studies it can be concluded both HEART score of this study are higher than others. These factors had been estimated 6.51± 1.84 and 3.71 ± 1.83 [2], 7.2 ± 1.7 and 3.8 ± 1.9 [12], 6.54± 1.7 and 3.96 ±2 [13] (all of them P=0.001) respectively in other studies. It can be mentioned age (Mean[SD]) was 60.85±14.09, lower in our study compared with previous study 61.2 ±15.4 [2].…”
Section: Discussionmentioning
confidence: 89%
“…In certain cases, a diagnosis can be made quickly, in particular in the case of an acute transmural myocardial infarction. Non-ST-elevation ACS (nTEACS), previously called unstable angina or pending infarction, typically causes uncertain 1,2 . This diagnosis can be made quickly in case of concurrent typical changes in the electrocardiogram (ECG) and/or increased levels of myocardial markers in plasma.…”
Section: Introductionmentioning
confidence: 99%